Fenomena Childfree dalam Pernikahan Perspektif Para Tokoh Nahdatul Ulama Kabupaten Subang - Muhammad Dimas Saputra; Muhammad Muhammad (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
The majority of married couples want to have children. However, as time goes by, many couples do not want children (childfree). Childfree has now become a lifestyle for several couples in several regions in Indonesia, including Subang Regency. The aim of this research is to answer various kinds of issues behind the presence of childfree in terms of the opinions of Nahdatul Ulama figures in Subang Regency. This type of research is field research. Researchers collected data by conducting interviews with childfree practitioners and several Nahdatul Ulama figures in Subang Regency in response to the childfree phenomenon. The results of the research reveal that there is a similarity in the opinions of the four Nahdatul Ulama figures from Subang Regency, namely that the majority do not agree with the existence of Childfree because it violates the maqāṣid al-Syarī'ah of the purpose of marriage itself, one of the most important of which is maintaining offspring (ḥifẓ al-nasl).